A retrospective review of substance use disorders amongst psychiatric inpatients at Chris Hani Baragwanath academic Hospital. - Motala, Zaahir Ahmad E. (My University, 2014)
Objective: Anecdotal evidence suggests that substance use is a significant problem among psychiatric patients admitted to Chris Hani Baragwanath Academic Hospital. The purpose of this study was to investigate the prevalence of substance use, the type of substance used and the socio-demographic and clinical factors associated with substance use among a group of psychiatric inpatients. Method: This study was a retrospective record review of all patients admitted to the psychiatric wards at Chris Hani Baragwanath Academic Hospital between the periods of July and December 2008. Results: Substance use was 4.8 (95% CI:2.7-8.4) times more likely among male subjects (p<0.001), 4.1 times (95%CI: 1.8-9.3) more likely in subjects aged 18-30 years compared to older patients (p=0.001), 3 times (95% CI: 1.2-7.4) more likely in subjects who were single (p=0.001), 1.9 (95% CI:1.4-2.7) times more likely in subjects who did not have children (p<0.001), and 1.5 (95% CI:1.2-2.1) times more likely in subjects with a psychotic disorder (p=0.004) compared to those with a mood disorder. Mood and psychotic disorders were compared and only the past psychiatric history was found to be significantly associated with psychotic disorders. Conclusion: Male gender was found to be significantly associated with substance use. Alcohol and cannabis were the most common substances used and polysubstance use also was a common occurrence. These findings have implications for preventative measures, psychiatric practice and specialized care for dual diagnosis patients.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Psychiatry, Johannesburg, September 2013
Keywords: Substance Abuse; Mental Disorders